Isolation of Potential Antifungal Agent Olean-12-ene-28-oic Acid-3-O-α-L-arabinofuranosyl(1→2)-α-Lrhamnopyranosyl( 1→4)-O-β-D-glucopyranoside from the Seeds of Jussiaea suffruticosa - BHARDWAJ, S.D. (Asian Journal of Chemistry, 2010)
The seeds of Jussiaea suffruticosa is plant were extracted with petroleum ether and methanol by using reflux condenser. The viscous mass extract from methanol yields a light yellow colour compound which responded to positive test for saponin. The antimicrobial activity of saponin was tested to posses high activity for inhibiting the growth of fungi.